Ultra-High\Spatial Resolution Basal and Evoked Cerebral Blood Flow MRI of the Rat Brain - Shen, Qiang (Brain Res, 2014)
Cerebral blood flow (CBF) is tightly coupled to metabolism and neural activity under normal physiological conditions, and is often perturbed in disease states. The goals of this study were to implement a high-resolution (up to 50×38 μm) CBF MRI protocol of the rat brain, create a digital CBF atlas, report CBF values for 30+ brain structures based on the atlas, and explore applications of high-resolution CBF fMRI of forepaw stimulation. Excellent blood-flow contrasts were observed among different cortical and subcortical structures. CBF MRI showed column-like alternating bright and dark bands in the neocortices, reflecting the layout of descending arterioles and ascending venules, respectively. CBF MRI also showed lamina-like alternating bright and dark layers across the cortical thicknesses, consistent with the underlying vascular density. CBF profiles across the cortical thickness showed two peaks in layer IV and VI and a shallow trough in layer V. Whole-brain CBF was about 0.89ml/g/min, with the highest CBF values found amongst the neocortical structures (1ml/g/min, range: 0.89–1.16ml/g/min) and the lowest CBF values in the corpus callosum (0.32ml/g/min), yielding a gray:white matter CBF ratio of 3.1. CBF fMRI responses peaked across layers IV–V, whereas the BOLD fMRI responses showed a peak in the superficial layers II–III. High-resolution basal CBF MRI, evoked CBF fMRI, and CBF brain atlas can be used to study neurological disorders (such as ischemic stroke).